High Level of Unwarranted Clinical Variation in the Use of Lower Extremity Revascularisation Procedures in Hungary (2013–2017). (June 2022) - Kolossváry, Endre; Ferenci, Tamás; Kováts, Tamás; Sótonyi, Péter; Szeberin, Zoltán; Nemes, Balázs; Dósa, Edit; Farkas, Katalin; Járai, Zoltán
Abstract : Objective: Assessment of variations in the use of lower extremity open vascular surgical procedures (LEOPEN) and lower extremity endovascular procedures (LEENDO) across small geographic areas in Hungary from 2013 to 2017. Introduction of a new metric giving a rough estimate of unwarranted clinical variation in revascularisation practice. Methods: Spatial variation (at local administrative unit level) of referral for LEOPEN and LEENDO was evaluated through a retrospective analysis using healthcare administrative data of all beneficiaries in Hungary. The same assessment was performed for percutaneous coronary intervention in acute myocardial infarction (PCIAMI). The latter was considered a reasonable comparator (similar at risk population, well organised, guideline driven patient pathways, small room for referral discretion). Consequently, the ratio of spatial variations of LEOPEN and LEENDO to PCIAMI (as a reference) are thought to reflect unwarranted clinical variation. Results: A total of 109 882 procedures were identified in the database (LEOPEN, LEENDO, PCIAMI) affecting 85 083 patients. While estimates of spatial variations for LEOPEN and LEENDO turned out to be high (systematic component of variation [SCV] 0.09 and 0.21, respectively), PCIAMI showed a low SCV value of 0.02. Consequently, the ratios of SCVs were SCV/SCVref = 4.67 (LEOPEN) and SCV/SCVref = 10.3 (LEENDO), indicating high levels of unwarranted clinical variation. Conclusion: The analysis showed that patients living in different locations of Hungary face very different odds of having lower extremity revascularisation procedures (open or endovascular). This spatial variation is thought to be related mainly to the failure in vascular service organisation. The newly introduced numerical estimate of unwarranted clinical variation may support within, and also between, system comparisons.